Analysis of Factors That Influence the use of Accounting Information by MSMEs - Rizqy Aiddha Yuniawati (MultiTech Publisher, 2023)
In general, the performance of small and medium enterprises (MSMEs) varies from year to year. The output growth rate of small and medium enterprises (MSMEs) changes every year. Financial management is one of the problems often faced by MSME. Although the impact of neglecting financial management may not be immediately visible, a potentially growing company can go bankrupt if it does not use proper accounting methods. There are several other challenges faced by MSMEs, such as a lack of accounting or bookkeeping knowledge, not having sufficient funds to hire an accountant or buy an accounting program that makes bookkeeping easier. It is hoped that this research can help micro and small businesses (MSMEs) make decisions about credit applications and tax calculations. MSME Community in Jenggawah, Jember in 2021 are the subject of this research. This research utilizes multiple linear regression analysis. The research results show that accounting knowledge behavior, firm age, and training on accounting have a significant effect on the use of accounting. In general, the performance of small and medium enterprises (MSMEs) varies from year to year. The output growth rate of small and medium enterprises (MSMEs) changes every year. Financial management is one of the problems often faced by MSME. Although the impact of neglecting financial management may not be immediately visible, a potentially growing company can go bankrupt if it does not use proper accounting methods. There are several other challenges faced by MSMEs, such as a lack of accounting or bookkeeping knowledge, not having sufficient funds to hire an accountant or buy an accounting program that makes bookkeeping easier. It is hoped that this research can help micro and small businesses (MSMEs) make decisions about credit applications and tax calculations. MSME Community in Jenggawah, Jember in 2021 are the subject of this research. This research utilizes multiple linear regression analysis. The research results show that accounting knowledge behavior, firm age, and training on accounting have a significant effect on the use of accounting.